Case study of stress ball implementation to reduce pain in children with dhf during blood sampling - Diki Ardiansyah; Asep Badrujamaludin; Rizki Endang Juliani; Dedi Supriadi (THE JOURNAL OF Mother and Child Health Concerns, 2026)
Background: Blood sampling is a common invasive procedure in children with suspected Dengue Hemorrhagic Fever (DHF). This procedure causes pain, non-pharmacological interventions to reduce pain with distraction techniques using stress balls. Purpose: This study aims to describe the effect of stress ball implementation in reducing pain in children aged 3-6 years who undergo blood sampling in the emergency room with a medical diagnosis of suspected DHF. Method: Descriptive method research in the form of a case study on one preschool child with a diagnosis of suspected DHF. Data were collected through interviews, observations, physical examinations, literature studies, and medical documentation. Results: The results of the assessment of breathing frequency 26x/min, SpO2 96%, BP 95/65 mmhg, pulse frequency 78x/min, CRT <2 seconds, complaining of pain on a scale of 5, grimacing, looking restless, with acute pain nursing problems. The results of the study showed that the use of stress balls during the blood sampling process at preschool age was able to reduce the level of pain from a moderate pain scale to mild pain through observation of children's verbal and non-verbal responses. Conclusion: Stress ball is proven to reduce pain during blood collection in preschool age. Suggestion: Therefore, this intervention can be applied more widely in health care facilities as part of standard paediatric nursing services.